2016
DOI: 10.3390/molecules21050673
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Xiang, S., et al. Schisandrin B Induces Apoptosis and Cell Cycle Arrest of Gallbladder Cancer Cells. Molecules 2014, 19, 13235–13250

Abstract: We apologize for any inconvenience brought to the readers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
0
1
Order By: Relevance
“…Different from previous studies (Song et al, 2011;Wang et al, 2011Wang et al, , 2012Zhang et al, 2013;Li et al, 2015Li et al, , 2016Ma et al, 2015;Xu et al, 2015;Ye et al, 2015;Han et al, 2016;Jiang et al, 2016), assessing the effects of microRNA-138 on tumor cells, our studying showed that miR-138-5p not only inhibits the proliferation of tumor cells but also regulates the tumor immune micro-environment. Lent-miR-138-5p treatment increased the number of tumor-infiltrated DCs and regulated the maturation of DCs in the A549/3LL-bearing mice model, and promoted DCs' capability to inhibit tumor cells and enhance T cells to kill tumor cells.…”
Section: Discussioncontrasting
confidence: 94%
“…Different from previous studies (Song et al, 2011;Wang et al, 2011Wang et al, , 2012Zhang et al, 2013;Li et al, 2015Li et al, , 2016Ma et al, 2015;Xu et al, 2015;Ye et al, 2015;Han et al, 2016;Jiang et al, 2016), assessing the effects of microRNA-138 on tumor cells, our studying showed that miR-138-5p not only inhibits the proliferation of tumor cells but also regulates the tumor immune micro-environment. Lent-miR-138-5p treatment increased the number of tumor-infiltrated DCs and regulated the maturation of DCs in the A549/3LL-bearing mice model, and promoted DCs' capability to inhibit tumor cells and enhance T cells to kill tumor cells.…”
Section: Discussioncontrasting
confidence: 94%